Periodic disturbance time interval for suppression of the maize weevils, Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) in stored maize (Zea mays L.). (December 2021) - Sserunjogi, M.; Bern, C.J.; Brumm, T.J.; Maier, D.E.
Abstract: Sitophilus zeamais Motschulsky threaten maize (Zea mays L.) storage in the tropical regions of low-income countries where maize is a staple. Disturbance of maize during storage can be an alternative to chemical treatment in suppressing populations of S. zeamais . Disturbance has been successful against insect pests of stored products, i.e. bean weevils, Acanthoscelides obtectus (say) (Coleoptera: Chysomelidae: Bruchinae) and lesser grain borers Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae). Prior research has not established a standard disturbance interval. This study tested various disturbance intervals to see determine suppression of S. zeamais populations in stored maize with four treatments: stationary jars (control) and jars disturbed at intervals of 8, 12 and 24 h. Jars contained 1 kg of 16 ± 0.7% wet basis moisture maize and 234 ± 51 adult S. zeamais stored at 27 °C, 70% r. h. and 12 h light and dark phases. Periodically, electric motors rotated jars through about 1.25 revolutions in 3 s. Three jars were selected randomly from each treatment every 40 d up to 160 d for analysis. Reduction in S. zeamais populations was 75%, 95% and 94% for 8, 12 and 24 h disturbance intervals, respectively, compared to the stationary jars after 160 d. The average quality of maize in all disturbed jars was better than in stationary jars, respectively, for moisture content (13 ± 1.1% vs. 21 ± 1.0%), bulk density (553.5 ± 1.1 kg/m 3 vs. 231.7 ± 1.2 kg/m 3 ), broken corn and foreign material (9 ± 1.2% vs. 68 ± 3.9%), insect damage (70 ± 4.5% vs. 100 ± 0.0%), and mold damage (0.4 ± 0.2% vs. 27 ± 17.2%). Disturbances of 12h and 24 h (once per day) proved the best intervals in suppressing S. zeamais populations and maintaining the quality of maize, much longer than previously reported. Of these two intervals, the less frequent 24 h disturbance interval may be an effective non-chemical approach to control S. zeamais in maize stored by smallholder farmers, requiring less effort. Highlights: Periodic disturbance suppresses insect pests in stored grain, but disturbance time interval has not been studied. Suppression of S . zeamais in maize with disturbance intervals of 8, 12 and 24 h and storage periods of up to 160 d was studied. 12 and 24 h disturbance intervals suppressed S. zeamais by >94% at 160 d of storage with improved maize quality. A 24 h disturbance interval may be most effective for smallholder farmers to suppress S. zeamais in stored maize.